Reação de cultivares de cana-de-açúcar à broca do colmo - Dinardo-Miranda, Leila Luci; Fracasso, Juliano Vilela [UNESP]; da Costa, Viviane Pereira; Dos Anjos, Ivan Antonio; Peixoto Lopes, Diego Olympio [UNESP] (FapUNIFESP (SciELO), 2013)
The objective of this study was to evaluate the reaction of ten sugarcane cultivars to Diatraea saccharalis under field conditions, using a randomized block design with treatments in factorial 2x10 with six replications. The first factor was represented by two levels of infestation (infested and not infested) by borer and the second one, by the ten sugarcane varieties (IAC87-3396, IAC91-1099, IACSP93-3046, IACSP94-2101, IACSP94-2094, IACSP94-4004, IACSP95-5000, IACSP96-3060, IACSP96-2042 and SP91-1115). The experiment was evaluated in two crop cycles: plant crop and first ratoon. All cultivars were attacked by the borer, being IACSP94-4004, IACSP96-2042 and SP91-1115 the most damaged cultivars with the highest infestation index. During the plant crop, plots infested by the borer presented higher fiber content than the ones not infested. During the first ratoon, non infested plants produced 10% less and presented lower purity and higher content of reducing sugars than the non-infested plants.
Reaction of sugarcane cultivars to sugarcane borer
Keywords: Diatraea saccharalis; Plant resistande to insects; Saccharum sp.; Technological analysis; Yield; bioaccumulation; crop damage; crop pest; crop plant; cropping practice; cultivar; experimental design; moth; pest resistance; sugar cane; yield response